Sharing Session Prospek Jurusan Manajemen - Kuntary Ibrahim, Isra Dewi; Rini Anggriani; Raden Bagus Faizal Irany Sidharta; Irwan Cahyadi; Ni Gusti Ayu Dasriani; Felicia Natalie Fedrich; Bintang Rizki Maulana (Insan Kreasi Media, 2023)
Students need knowledges about job prospects after graduating from the institutions so this activity is carried out using the sharing session/knowledge sharing method and the results of this service are 1) There is an increase in student and prospective students' knowledge about the prospects for management majors with 3 (three) concentrations both Management Human Resources, Marketing and Finance and 2) Be able to know and have a picture of how the world of work is in accordance with the knowledge gained during college and current job opportunities majoring in management, and 3) Can motivate students to study diligently and actively according to majors and concentrations he chooses to become graduates who are specialized and qualified and ready to work anywhere in accordance with the current needs of the world of work and industry.